2019
DOI: 10.4103/jfmpc.jfmpc_348_19
|View full text |Cite
|
Sign up to set email alerts
|

A study of the cardiac risk factors emerging out of subclinical hypothyroidism

Abstract: Introduction: Subclinical hypothyroidism is defined as a serum TSH level above the upper limit of normal with normal levels of serum free thyroxine. It is a common thyroid disorder affecting 3-15% of the adult population. Aims and objectives: To study the cardiovascular profile of patients with subclinical hypothyroidism, and to establish cardiac risk factors emerging out of subclinical hypothyroidism. Methodology: Adult patients attending Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
(17 reference statements)
1
9
0
4
Order By: Relevance
“…Compared with euthyroid individuals, patients with SHypo have significantly elevated levels of total cholesterol (TC), triglycerides (TG), and low-density lipoprotein-cholesterol (LDL-C) levels and significantly decreased levels of high-density lipoprotein-cholesterol (HDL-C) [37][38][39][40]. Such a change is observed with increasing TSH even when TSH is within International Journal of Endocrinology normal range.…”
Section: Dyslipidemia and Yroid Functionmentioning
confidence: 99%
“…Compared with euthyroid individuals, patients with SHypo have significantly elevated levels of total cholesterol (TC), triglycerides (TG), and low-density lipoprotein-cholesterol (LDL-C) levels and significantly decreased levels of high-density lipoprotein-cholesterol (HDL-C) [37][38][39][40]. Such a change is observed with increasing TSH even when TSH is within International Journal of Endocrinology normal range.…”
Section: Dyslipidemia and Yroid Functionmentioning
confidence: 99%
“…Although patients with overt hypothyroidism often complain of weight gain, the association between SH and weight was less clear, especially in AH patients. Dey A., Kanneganti V., Das D. (2019) found that among SH patients with a mean age of 35.1 ± 10.26 years, 12 % were overweight, 24 % were obese, 44 % had a high waist-to-hip ratio, indicating on central obesity, 20 % had high both BMI and waist-to-hip ratio [13]. A significant relationship between central obesity and SH was found by T. M. J. Santhoshakumari, M. Sneha (2019) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Демонстрируются противоречивые данные. Авторы указывают на прогрессирование течения дислипидемии, что ведет к прогрессированию коронарного атеросклероза, однако в некоторых источниках указывается на отсутствие статистически значимых ассоциаций гипотиреоза со степенью коронарного атеросклероза [11]. В проведенном нами исследовании обнаружены статистически значимые данные, указывающие на преобладание трехсосудистого поражения коронарных сосудов в группе пациентов с ИБС на фоне первичного манифестного гипотиреоза по сравнению с группой пациентов с ИБС без гипотиреоза.…”
Section: Discussionunclassified
“…Выделяются три основных механизма влияния дисбаланса гормонов щитовидной железы на течение ССЗ: • прямое геномное воздействие на кардиомиоциты через сопряжение с ядерными рецепторами, что, в свою очередь, приводит к регуляции экспрессии генов-мишеней; • внеядерный механизм -влияние гормонов на ионные каналы в клеточной мембране кардиомиоцитов; • экстракардиальный механизм -различные эффекты трийодтиронина (Т3) и тироксина (Т4) на периферическое кровообращение, изменение параметров сердечно-сосудистой гемодинамики, показатели сократимости миокарда (ударный объем) и т. д. [10,11]. Все вышеперечисленные патогенетические механизмы ведут к ухудшению течения ССЗ на фоне гипотиреоза.…”
Section: заключениеunclassified